Creator’s freedom. Schulz’s late projects - Szyszka vel Syska, Monika (Acta Universitatis Lodziensis. Folia Litteraria Polonica, 2018)
The article discusses the idea of creation coined by authors descended from the same, Austro-Hungarian cultural field, by: Bruno Schulz, Joseph Roth and Gustav Meyrink. Austro-Hungarian Monarchy created its own mithology based on nostalgia for the World, which was consigning to the dark recesses of history. The authors, conscious of inefficiency of contemporary culture, used the idea of Demiurge to show one of possible creating ideas.